Makassar’s Electoral Trust: Identifikasi Karakter Personal sebagai Preferensi Kepercayaan Pemilih Pemula - Rhesa, Muhammad; Firmansyah, Muhammad Reza (Universitas Negeri Makassar, 2025)
It is noted that public participation rates in general elections in Indonesia have declined annually, illustrating a phenomenon of disconnected electoral as part of distrust, where there is a disconnect between representatives and the represented. This issue can influence political perceptions and public trust in mayoral candidates, particularly among young first-time voters. Therefore, this study aims to examine the role of personal attributes (benevolence, competence, integrity) of Makassar mayoral candidates in influencing the trust of first-time voters. This quantitative study used a sample of 104 first-time voters aged 17-23 years. The results showed that benevolence, competence, and integrity influence trust by 69.5%, with benevolence having no significant effect (p=0.717). In the group of participants who knew the mayoral candidates, competence and integrity influenced trust by 73.9%, while benevolence had no significant effect (p=0.846). In the group of participants who did not know the mayoral candidates, benevolence, competence, and integrity influenced trust by 71.7%. Furthermore, 66% of first-time voters desire a Makassar mayoral candidate with integrity in their future leadership.